2018
DOI: 10.1590/0104-1428.02416
|View full text |Cite
|
Sign up to set email alerts
|

Use of chitosan in the remediation of water from purification of biodiesel

Abstract: ObstractThis article evaluates the efficiency of the degradation of pollutants present in water from the purification of biodiesel, characterized by high content of chemical oxygen demand (COD), suspended solids (SS), oils and greases, methanol, soap, and glycerol. The treatment process proposed was of the photo-Fenton type using iron immobilized in chitosan. The characterization of the material was performed according to degree of deacetylation (DD) and thermal stability (TG). The results revealed a DD of 66.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
4
0
2
Order By: Relevance
“…Otros autores reportaron que se ha logrado disminuir la DQO en aguas de la industria sardinera y se tienen registros de valores aproximados de 30 mg L -1 y reducciones cercanas al 70 % al centrifugar el agua de estudio y luego usar dosis de quitosano de 100 y 1000 mg L -1 con pH de evaluación de 4 a 7 (Pacheco-Aguilar et al, 2009). También, en aguas residuales de una planta procesadora de biodiesel se alcanzaron remociones del 94 % de DQO mediante un proceso Foto-Fenton que incluyó la evaluación de hierro inmovilizado en quitosano (Stroparo et al, 2018).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Otros autores reportaron que se ha logrado disminuir la DQO en aguas de la industria sardinera y se tienen registros de valores aproximados de 30 mg L -1 y reducciones cercanas al 70 % al centrifugar el agua de estudio y luego usar dosis de quitosano de 100 y 1000 mg L -1 con pH de evaluación de 4 a 7 (Pacheco-Aguilar et al, 2009). También, en aguas residuales de una planta procesadora de biodiesel se alcanzaron remociones del 94 % de DQO mediante un proceso Foto-Fenton que incluyó la evaluación de hierro inmovilizado en quitosano (Stroparo et al, 2018).…”
Section: Discussionunclassified
“…Se ha encontrado una influencia significativa de la dosis de este biopolímero sobre parámetros fisicoquímicos del agua derivada de producción de aceite de palma (Ahmad et al, 2006). Además, en la industria sardinera, dosis de quitosano de 200 a 1000 mg L -1 , han logrado reducir la demanda química de oxígeno (DQO) presente en el agua residual (Pacheco-Aguilar et al, 2009); mientras que en efluentes de una planta procesadora de biodiesel, se han reportado reducciones de este parámetro hasta del 94 % al usar el quitosano como un componente del tratamiento biorremediador (Stroparo et al, 2018).…”
Section: Introductionunclassified
“…00, No. 00, 2022 amine and acetyl surface groups (stage I) and glucopyranose of CS (stage II), 70,71 leaving 21.1% residue at 800 °C (Figures 4b, 4d). On the other hand, CS/NPK exhibited increased thermal stability that started below 240 °C, showing more intense and separated mass loss in two stages at 286 °C (T max1 ) and 356 °C (T max2 ).…”
Section: Adsorption Capability Of Scb Derivativesmentioning
confidence: 99%
“…While Daud et al (2018) reported the removal of turbidity, COD, and soluble solids (32%, 34%, and 39%, respectively). Stroparo et al (2018) evaluated the use of chitosan as an alternative to the conventional chemicals and reported removals of 94% and 70% of COD and O&G, respectively; although the reduction in pollutant compounds presented by the authors was high, the wide range of contaminants present in the BW must be considered.…”
Section: Conventional Treatment Of Bwmentioning
confidence: 99%